Impact of surgical approach and resection technique on the risk of Trifecta Failure after partial nephrectomy for highly complex renal masses. Issue 3 (March 2022) - Campi, Riccardo; Di Maida, Fabrizio; Lane, Brian R.; De Cobelli, Ottavio; Sanguedolce, Francesco; Hatzichristodoulou, Georgios; Antonelli, Alessandro; Noyes, Sabrina; Mari, Andrea; Grosso, Antonio Andrea; Rodriguez-Faba, Oscar; Keeley, Frank X.; et al.
Abstract: Introduction: We aimed to compare the outcomes of open vs robotic partial nephrectomy (PN), focusing on predictors of Trifecta failure in patients with highly complex renal masses. Patients and methods: We queried the prospectively collected database from the SIB International Consortium, including 507 consecutive patients with cT1-2N0M0 renal masses treated at 16 high-volume referral centres, to select those with highly complex (PADUA score ≥10) tumors undergoing PN. RT was classified as enucleation, enucleoresection or resection according to the SIB score. Trifecta was defined as achievement of negative surgical margins, no acute kidney injury and no Clavien-Dindo grade ≥2 postoperative surgical complications. Multivariable logistic regression analysis was used to assess independent predictors of Trifecta failure. Results: 113 patients were included. Patients undergoing open PN (n = 47, 41.6%) and robotic PN (n = 66, 58.4%) were comparable in baseline characteristics. RT was classified as enucleation, enucleoresection and resection in 46.9%, 34.0% and 19.1% of open PN, and in 50.0%, 40.9% and 9.1% of robotic PN (p = 0.28). Trifecta was achieved in significantly more patients after robotic PN (69.7% vs. 42.6%, p = 0.004). On multivariable analysis, surgical approach (open vs robotic, OR: 2.62; 95%CI: 1.11–6.15, p = 0.027) and tumor complexity (OR for each additional unit of the PADUA score: 2.27; 95%CI: 1.27–4.06, p = 0.006) were significant predictors of Trifecta failure, while RT was not. The study is limited by lack of randomization; as such, selection bias and confounding cannot be entirely ruled out. Conclusions: Tumor complexity and surgical approach were independent predictors of Trifecta failure after PN for highly complex renal masses.